12. RESEARCH ON NEONATAL MORTALITY IN THE PEDIATRIC CENTER OF BACH MAI HOSPITAL (Vietnam Journal of Community Medicine, 2023)
Objective: To study neonatal mortality in the pediatric center of Bach Mai Hospital. Subject and methods: A descriptive study was conducted on 373 neonatal admitted to the pediatric center of Bach Mai Hospital. Results: Of the 373 hospitalized infants, 32 died, accounting for 8.6%. Most newborns hospitalized on the first day accounted for 70% (261/373). About 68.8 % of neonatal deaths occurred in the first week, and the mortality rate gradually decreased over time, with a rate of 15.6% in the second week, 9.4% in the third week, and 6.2% in the fourth week. In the first week, mortality was mainly in the first three days after giving birth, with a rate of 56.3%. Preterm birth with complications is a leading cause of death in neonatal with a rate of 37.5%, followed by perinatal asphyxia with a rate of 34.4%. Two causes of birth defects and neonatal sepsis with rates of 21.9% and 6.3%, respectively. Conclusion: The rate of neonatal mortality is still relatively high. Most newborns admitted to the hospital are preterm. Most infant deaths occur in the first week after birth. The preterm birth with complications postpartum asphyxia is a leading cause of death in neonatal.
Keywords: Neonatal mortality, pediatric center, Bach Mai hospital, preterm birth.